Farmers and herders unite - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Relations between farmers and herders are often a source of conflict, in the Sahel as elsewhere. Each of them claims the right to use and manage the natural resources of water, land and forage. In Beiga, in northern Burkina Faso, local people have...